Kiprah Kader Nasyi’atul ‘Aisyiyah dalam Meningkatkan Kesehatan Mental Perempuan - Fatiah Handayani; Lutfah ‘Aisyah Amini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Mental health is a part of the overall health of a human being. Mental health is a fundamental component of the definition of health. Good mental health allows people to realize their potential, cope with the stresses of normal life, work productively, and contribute to their communities. The obligations of lecturers in tertiary institutions are the tri dharma of higher education, namely education and teaching, research, and Community Service. The purpose of this PkM activity is to provide information about mental health to women, especially during the Covid-19 pandemic, through seminars held online for youth cadres of the Muhammadiyah organization. The method used is online/online seminars through the Google Meet application. Google Meet is an online video-conferencing application. The material was given in PowerPoint with the number of targets during the activity, namely 21 people from Muhammadiyah autonomous organizations. Data collection for evaluation was carried out through discussion and question-and-answer sessions. The activity results showed that five participants asked questions about the material provided. The next recommendation was that the participants' reach should be more through massive and structured information dissemination with media tailored to the capacity of the targeted participants.